E-Kimia / Muraleedharan - Muraleedharan, - (2003)
Online learning module for STPM chemistry is a web-based multimedia system that can provide information on STPM chemistry. Besides being an online tutor, it also offers search capability and real-time quizzes. The system focuses on delivering content, which are the basics for STPM chemistry for better understanding of the subject and also enable non-students to benefit from it. The findings in the Literature Review were made as a reference to choose the right tools to develop this system, which is data driven and has multimedia enhancements. In reviewing the tools to fulfill such requirements, Active Server Pages (ASP), Hypertext Markup Language (HTML), Virtual Reality Markup Language (VRML), VBScript and JavaScript seemed appropriate to program the system. The system will be developed in Windows 98 environment, thus related software packages such as using the Macromedia Dreamweaver, Microsoft FrontPage, Microsoft Access, Personal Web Server (PWS), Adobe Photoshop, and Macromedia Flash will be used. The waterfall model together with Data Flow Diagram the two method that will be referred to develop the system. The final requirements are met in the System Analysis and the system is designed in various forms in System Design. Finally after the proposal stages are complete the system will be developed, implemented, tested and refined.